The misinformation effect in financial markets: An emerging issue in behavioural fianance - Mateusz Polak (e-Finanse: Financial Internet Quarterly, 2012)
The following paper is a theoretical introduction of the misinformation effect to behavioural finance. The misinformation effect causes a memory report regarding an event or particular knowledge to become contaminated with misleading information from another source. The paper aims to describe possible impact of the aforementioned phenomenon on the interpretation of stock market data, as well as the consequences of misinformation on investment-related decisions and the effective market hypothesis.
Keywords: A12; G02; G14; 330; behavioural finance; stock market psychology; misinformation effect; Anlageverhalten; Asymmetrische Information; Wirtschaftspsychologie; Aktienmarkt; Theorie